2014
DOI: 10.1111/echo.12639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Left Atrial Performance in Patients with Type 2 Diabetes Mellitus without Overt Cardiac Disease and Inducible Ischemia: High Prevalence of Increased Systolic Force Related to Enhanced Left Ventricular Systolic Longitudinal Function

Abstract: High LASF is present in one third of T2DM patients without overt cardiac disease and is positively and independently related to an increased LV longitudinal shortening function, suggesting a close interaction between LV systolic and diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that both LA size and function are markers of LV diastolic dysfunction and prognostic markers for adverse cardiovascular events [ 4 , 5 , 15 ]. However, those studies focused on volume or mechanics, and none has quantitatively assessed LA blood flow dynamics in T2DM patients and the relationship with glycemic control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that both LA size and function are markers of LV diastolic dysfunction and prognostic markers for adverse cardiovascular events [ 4 , 5 , 15 ]. However, those studies focused on volume or mechanics, and none has quantitatively assessed LA blood flow dynamics in T2DM patients and the relationship with glycemic control.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a useful indicator of the efficiency of blood flow transfer and can reflect superfluous cardiac afterload caused by turbulent flow [ 17 ]. On the other hand, LA mechanics are impaired in T2DM patients [ 5 ]. With advances in the non-invasive evaluation of atrial function, STE is increasingly used to assess LA function, given its relative angle independence and ability to assess global atrial mechanics [ 9 ].…”
Section: Introductionmentioning
confidence: 99%